Memahami Konflik Radikalisme dan Anarkisme dalam Masyarakat Modern - Muhammad Nawir; Sam'un Mukramin; Lukman Ismail; Maemunah Maemunah; Irma Rachmawati (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This paper focuses on the conflict of radicalism and anarchism in contemporary society. This research is qualitative with a literature review. The literature collected comes from several national and international articles, proceedings, books, and other references related to the issue of radicalism and anarchism in a global society. The data analysis is carried out by reviewing related references and looking for unique points to find findings in the study. This study finds that a strong ideology influences society, so understanding the conflict between radicalism and anarchism in modern society also develops.